Implementasi Mobilisasi Sosial dalam Pengendalian Tuberkulosis Paru di Puskesmas Siko dan Kalumata Kota Ternate - Muliana Muliana; Fauzi Almari (FORIKES, 2022)
Controlling tuberculosis (TB) is the responsibility of all elements including the government, health workers and the community. Social mobilization is a process of providing information continuously following the development of targets and helping them so that they have the knowledge, attitudes and practice the expected behavior. The purpose of this study was to determine the implementation of social mobilization in TB control at the Siko and Kalumata Health Centers, Ternate City. The research method used was mixed methods, with a concurrent triangulation design. The samples in this study were 30 TB patients at the Kalumata Health Center and 20 TB patients at the Siko Health Center, which were selected using a total population sampling technique. Data was collected through interviews, documentation studies and visual materials. The results showed that for social mobilization there were 26.0% in the less category and 74.0% in the sufficient category. Statistically, social mobilization among Siko Health Centers is higher than that of Kalumata Health Centers. It was also found that there were differences in the outreach program and patient home visits between the Siko Health Center and the Kalumata Health Center. Based on the results of the study, it is deemed important to maximize the function of education to the community, especially for TB patients, to build partnerships with community leaders and health cadres, as well as a more creative approach and guidelines for social mobilization for TB control.Keywords: pulmonary tuberculosis; social mobilization ABSTRAK Penanggulangan tuberkulosis (TB) merupakan tanggungjawab seluruh elemen antara lain pemerintah, petugas kesehatan dan masyarakat. Mobilisasi sosial merupakan proses pemberian informasi secara terus menerus mengikuti perkembangan sasaran dan membantu mereka sehingga memiliki pengetahuan, sikap dan mempraktikan perilaku yang diharapkan. Tujuan penelitian ini adalah untuk mengetahui implementasi mobilisasi sosial dalam pengendalian TB di Puskesmas Siko dan Kalumata Kota Ternate. Metode penelitian yang digunakan yaitu mixed methods, dengan desain concurrent triangulation. Sampel dalam penelitian adalah 30 pasien TB di Puskesmas Kalumata dan 20 pasien TB di Puskesmas Siko, yang dipilih dengan teknik total population sampling. Pengumpulan data dilakukan melalui wawancara, studi dokumentasi dan materi-materi visual. Hasil penelitian menunjukkan bahwa untuk mobilasisasi sosial terdapat 26,0% dengan kategori kurang dan 74,0% dengan kategori cukup. Secara statistik, mobilisasi sosial antara Puskesmas Siko lebih tinggi daripada Puskesmas Kalumata. Juga ditemukan bahwa ada perbedaan program penyuluhan dan kunjungan rumah pasien antara Puskesmas Siko dan Puskesmas Kalumata. Berdasarkan hasil penelitian dipandang penting untuk memaksimalkan fungsi edukasi kepada masyarakat terutama bagi pasien TB, membangun kemitraan dengan tokoh masyarakat dan kader kesehatan, juga diperlukan pendekatan yang lebih kreatif dan pedoman mobilisasi sosial pengendalian TB.Kata Kunci: tuberkulosis paru; mobilisasi sosial